The effect of nickel, cobalt and tin on the evolution of microstructural and mechanical properties of Al-Zn-Mg-Cu alloys (7000 series) via casting, powder metallurgy and friction stir processing techniques - Naeem, Haider T. (School of Materials Engineering, 2015)
The main objective of this study was to improve the microstructural, mechanical; corrosion and solid particle erosion behaviour of Al-Zn-Mg-Cu alloys, since are proposed to cope with new aviation and military requirements. This objective was attained through following the routes mentioned below; to manufacture the new series of high strength Al-Zn-Mg-Cu alloys with additives of nickel, tin and cobalt via a semi direct chill casting process; to examine and analyse the effect of intermetallic compounds of Ni, Co and Sn as well as the precipitate phases of alloying elements within the matrix of Al-alloys which underwent the hot extrusion process and subsequent treatment of the aging and retrogression and reaging process and to examine impact of compounds on the microstructural, mechanical properties and resistance to corrosion/erosion of the Al-Zn-Mg-Cu alloys.